Computer Graphics - Sinha, Amarenda N.; Udai, Arun D. (New Delhi, 2008)
This book provides an introduction to Computer Graphics, covering all topics from the principles, techniques employed and their applications. Every effort has been made to present a balanced coverage of theory and practical applications in Computer Graphics. The book is designed as a text for either a one-or two-semester course at the undergraduate or first-year postgraduate level. It can also be used for self-study.
Keywords: Computer Graphics